2008
DOI: 10.1002/ajh.21214
|View full text |Cite
|
Sign up to set email alerts
|

Late reactivation of resolved hepatitis B virus infection: An increasing complication post rituximab‐based regimens treatment?

Abstract: Reactivation of hepatitis B infection is an increasing problem for patients with lymphoma, even in resolved infections, who were treated with rituximab-based regimens. Our cases point out the need of prolonged prophylaxis in HBsAg-negative patients due to the high risk of developing fatal reactivation. Am. J. Hematol. 83:673-675, 2008. V

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(30 citation statements)
references
References 20 publications
0
28
0
2
Order By: Relevance
“…In addition, it is not fully understood how long the pharmacological prophylaxis should last in order to prevent the reactivation of HBV infection. Observational studies suggest extending the prophylaxis to the 12 th month after the discontinuation of immunosuppressive treatment, but in some case reports HBV reactivation occurred later, especially in patients treated with rituximab [39,90] . Recently, Tonziello et al [39] described a reactivation of OBI in an HBsAgnegative/anti-HBc-positive woman with non-Hodgkin lymphoma occurring 20 mo after rituximab discontinuation despite lamivudine prophylaxis covering the 4 mo of rituximab administration and the 12 mo after its discontinuation.…”
Section: Infectionmentioning
confidence: 99%
“…In addition, it is not fully understood how long the pharmacological prophylaxis should last in order to prevent the reactivation of HBV infection. Observational studies suggest extending the prophylaxis to the 12 th month after the discontinuation of immunosuppressive treatment, but in some case reports HBV reactivation occurred later, especially in patients treated with rituximab [39,90] . Recently, Tonziello et al [39] described a reactivation of OBI in an HBsAgnegative/anti-HBc-positive woman with non-Hodgkin lymphoma occurring 20 mo after rituximab discontinuation despite lamivudine prophylaxis covering the 4 mo of rituximab administration and the 12 mo after its discontinuation.…”
Section: Infectionmentioning
confidence: 99%
“…The 2007 guidelines by Lok et al [50] are more specific than past guidelines and include a recommendation to extend the period of preventive lamivudine treatment, depending on HBV-DNA monitoring results. Some research reported a delayed onset of the HBV reactivation with rituximab therapy [69][70][71] . We also observed a case in which HBV reactivation was detected 4 years after chemotherapy and preventive lamivudine administration had been completed.…”
Section: Nucleoside Analog Treatment For the Prevention Of Hbv Reactimentioning
confidence: 99%
“…Actually, many cases of rituximab-associated hepatitis B have been reported. [15][16][17][18][19] When ROR of hepatitis B associated with each drug (Table 2) was compared with that in the absence of a concomitant drug, as shown in Table 3, no signal was detected in cyclophosphamide or vincristine, suggesting that drugs concomitantly administered in R-CHOP therapy, such as rituximab, increased the number of hepatitis B cases to the high rank. RORs of rituximab and prednisolone were higher than those of the other drugs in Table 3, suggesting that these drugs are more strongly associated with hepatitis B development than the other drugs.…”
Section: Discussionmentioning
confidence: 99%